Animal model of rapid crystalloid infusion in rats - Orgaes, Flavio Stillitano [UNESP]; Viterbo, Fausto [UNESP]; Mendes, Flavio Henrique [UNESP]; Yabiku, Renato Florio [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To describe an animal model of rapid intravenous infusion with different volumes of crystalloid and discuss the clinical findings. METHODS: Fifty six male Wistar rats were used, divided randomly in seven groups (n = 8). The rats of groups 1 to 6 received lactated Ringer´s solution intravenously, in the rate of 25 ml/min, with different volumes proportional to blood volume (BV). The rats of group 0 were submitted to the same procedure, but did not receive the fluid (control group). The data included respiratory rate, heart rate, saturation of peripheral oxygen (SpO2) in two times (before and after the infusion), and upshots (respiratory arrest and death). Dunnett´s test and ANOVA were used. RESULTS: The clinical signs significantly changed in the 2, 2.5 and 3 fold BV groups. The respiratory arrest was observed in the 1.5, 2, 2.5 and 3 fold BV groups, but death was present only in 2.5 and 3 fold BV groups. CONCLUSIONS: The infusion of crystalloid in the same volume of blood volume did not cause significant variation in respiratory and heart rate, saturation of peripheral oxygen and did not induce respiratory arrest. The infusion of a volume of 3 fold blood volume was lethal to all animals.
Keywords: Fluid Therapy; Hemodilution; Pulmonary Edema; Models, Animal; Rats